The interpretation of the flesh : Freud and femininity - Brennan, Teresa, 1952-2003 (Routledge, 1992)
The 'riddle of femininity', like Freud's reference to women's sexuality as a 'dark continent', has been treated as a romantic aside or a sexist evasion rather than as a problem to be solved. In this first comprehensive study, Teresa Brennan suggests that by placing these ideas in the context of Freud's work as a whole, we will begin to understand why femininity was such a riddle for Freud. Brennan argues that by turning to Freud's work and his concrete questions about femininity, a psychical state which occurs in men and women alike, the problem is clearly a soluble one, provided that Freud's concern with energy is taken into account. The real riddle of femininity is as much a problem for thinking about physicality as a problem for the subject who suffers from what Freud described as 'femininity's negative effects on curiosity, intelligence and activity.